Role of Ga-doping in iron-gallium alloy clusters - 汤沛哲 刘海涛 朱洁 王山鹰 段文晖 (Chinese physics B, 2012)
The structural and magnetic properties of Fen-mCam （n = 3 - 6, m = 0 - 2; n = 13, m = 0 - 3） alloy clusters have been studied using density functional theory. The substitutional doping is favourable for small clusters with up to six atoms at low Ga concentration and substitutional Ga atoms in 13-atom clusters prefer surface sites. The Ca-doping generally could reduce the energetic stability but enhance the electronic stability of Fe clusters, along with a decrease of the local magnetic moments of Fe atoms around Ca dopants. These findings provide a microscopic insight into Fe-Ga alloys which are well：known magnetostriction materials.